2022
DOI: 10.1007/s10803-022-05435-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Perspectives on Telehealth Assessment of Autism Spectrum Disorder During the COVID-19 Pandemic

Abstract: This study examined clinician insights into telehealth assessment services for autism spectrum disorder implemented during the COVID-19 pandemic. 35 clinicians from multiple disciplines across 17 sites in the Autism Care Network were interviewed. Themes identified through qualitative analyses included factors related to confidence in diagnosis (impressions of in-home observation; child and family factors that affected diagnostic confidence; changes in rapport); patient and family factors related to telehealth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
4
10
0
Order By: Relevance
“…The findings reported here are broadly consistent with those outlined in a handful of recent studies examining professionals’ experiences of providing telehealth autism diagnostic assessments in the United States and Australia [ 13 , 16 , 19 ]. Studies have reported that professionals appreciated the convenience, flexibility, efficiency, and cost and space savings of telehealth.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The findings reported here are broadly consistent with those outlined in a handful of recent studies examining professionals’ experiences of providing telehealth autism diagnostic assessments in the United States and Australia [ 13 , 16 , 19 ]. Studies have reported that professionals appreciated the convenience, flexibility, efficiency, and cost and space savings of telehealth.…”
Section: Discussionsupporting
confidence: 90%
“…Although internet use has broadly increased over the past decade (from 79.7% to 90% of the United Kingdom adult population), it is a cause for concern that individuals with longer-term health issues or from lower socioeconomic status backgrounds may be excluded from telehealth opportunities, or lack access to skill-based training or support to use this. In addition, poorer than required computer literacy of patients, their families, and professionals was highlighted as an important consideration in this study, mirroring findings elsewhere [ 13 , 16 ]. The unexpected onset of the COVID-19 pandemic is likely to have meant that some services were unable to swiftly assess digital poverty and competencies of patients, families, and professionals and accommodate needs accordingly.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations